UGLEVODLAR TEMASÍN OQÍTÍWDA INNOVACION TEXNOLOGIYALAR USÍLLARÍNAN PAYDALANÍW - Sh.Zaripbaev, K.; Dabilov, N.A.; Aytbaeva, X.B. (SCIENCE and SOCIETY, 2024)
This article presents the works and proposals of the authors on organizing classes using problem-based technology, assessment methods and a case in chemistry lessons. The examples show that methods based on the conducted methodological work are effective in teaching. These methods increase students’ creativity and activity.